Satellite Earth Observations and Their Impact on Society and Policy - Onoda, Masami; Young, Oran R; Onoda, Masami; Young, Oran R (Cham Springer Nature, 2017)
observation-based policy; environment; big data
English
Keywords: Environmental science, engineering & technology; observation-based policy; environment; big data